Emerging non-thermal technologies in the food industry: Advances and potential applications in food processing - Paucar-Menacho, Luz María (2024)
Currently, the food industry prioritizes the safety and quality of products, facing the challenge of maintaining sensory and nutritional integrity. To address this challenge, emerging non-thermal technologies are being explored that offer significant advantages in improving food quality over conventional technologies. This review aims to provide a comprehensive understanding of how these innovative technologies can transform the traditional food processing landscape as we know it. Non-thermal technologies have the potential to reduce energy consumption for food production, processing and packaging, compared to conventional thermal treatments. Furthermore, these technologies are particularly suitable for efficiently preserving bioactive compounds present in foods. This review describes the fundamental principles, applications, advantages and limitations of emerging technologies in food processing. These technologies include pulsed electric field, ultrasound, cold plasma, high pressure, irradiation, light-emitting diodes, pulsed light and oscillating magnetic fields. Despite the large number of studies on the subject, more research is required to optimize and improve the efficiency of the application of these technologies, alone or in combination, in food processing. The bioaccessibility and bioactivity of the compounds, nutritional value, shelf life and sensory aspects may be variables of interest.